Determinants of Firm Value in Banking Companies in Indonesia - Femba Akris Diantoro; Ahmad Roziq; Wahyu Agus Winarno (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
This study aims to of the variables determining the value of banking companies in the 2018-2020 period, sample selection using purposive sampling, which used the annual financial statements of banking companies. Research using path analysis results in research that Liquidity, firm size, capital structure is not significant to the value of dividend policy dividend significant effect. Liquidity, company size, capital structure and policies dividends are not significant to firm value, while profitability is significant to firm value. The implication of banking companies for issuers in Indonesia is that with the awareness that issuers have of the importance of company value, it must be maintained properly, because it can be influenced by a separate thought or perception of investment, and companies in increasing company performance. The implications of the theoretical benefits of this research are expected to provide information or contribute to the development of existing theories in Indonesia, so that academics can get enough information for further research on firm value.